Evolution of pastoralism in Southern Greenland during the last two millennia reconstructed from bile acids and coprophilous fungal spores in lacustrine sediments. (April 2015) - Guillemot, Typhaine; Zocatelli, Renata; Bichet, Vincent; Jacob, Jérémy; Massa, Charly; Le Milbeau, Claude; Richard, Hervé; Gauthier, Emilie
Abstract: To reconstruct the evolution of livestock in SW Greenland over the last two millennia, we measured the concentration of bile acids in a sedimentary sequence retrieved from Lake Igaliku. Deoxycholic acid (DOC) was the sole bile acid and was present throughout the sequence. The DOC flux correlated quantitatively with that of coprophilous fungal spores. Maximum DOC and coprophilous fungal spores flux was recorded during the two periods of human settlement and grazing activity in the region (i.e. the Norse settlement during the Middle Ages and the recent Danish agricultural phase since 1920). These flux values were consistent with the presence of recent livestock around the lake and are attested to by way of archeological data relating to the Norse period. In contrast, the DOC and coprophilous fungal spores background during pre-Norse times and the Little Ice Age (LIA), indicated the presence of wild herbivores. Lower DOC and coprophilous fungal spore flux values after the Norse abandonment, compared with pre-colonization conditions, could indicate that Norse activity in conjunction with climate change, altered the pristine wildlife. Therefore, these quantitative correlations between DOC flux and coprophilous fungal spores flux potentially suggest a quantitative relationship with the livestock grazing in the catchment. The comparison between sedimentary DOC and coprophilous fungal spores provides significant highlights on past pastoral dynamics over the last 2000 yr in SW Greenland.